Effect of ammonium-clinoptilolite on the growth of amaranthus gangeticus - Hamzah, Niza Syafiqah (2014)
The use of ammonium-clinoptilolite as fertilizer for Amaranthus gangeticus offers an option to reduce the environmental pollution problems such as nitrogen contamination in the air and water. In addition, nitrogen from ammonium plays important role in the growth of the plant especially on the leaf growth. High surface area and cation exchange capacity of zeolite type clinoptilolite was used as carrier to control ammonium release. In this study, the effect of ammoniumclinoptilolite (zeolite pre-load with ammonium (NH4+)) on Amaranthus gangeticus growth was studied. The study indicated that the results of plant heights and leaf number obtained fertilized with ammonium-clinoptilolite were higher compared to control sample (without ammonium).The result shows that the ammoniumclinoptilolite was a good carrier of nitrogen for Amaranthus gangeticus.